The job satisfaction of university teachers - Fatwa Tentama; Netty Merdiaty; Subardjo Subardjo (Journal of Education and Learning (EduLearn), 2021)
Employee job satisfaction is an important factor that can determine organizational productivity, and organizations need to pay attention to this pivotal aspect. This study aimed to empirically examine the role of transformational leadership styles and employability on employee job satisfaction. The participants of this study are 49 university teachers at the University of X Yogyakarta. The sampling is randomly chosen using a simple random sampling technique. In addition, data are collected using the scale of job satisfaction, the scale of transformational leadership style, and scale of employability. The data are then analyzed using multiple linear regression techniques. The results showed that 1) Simultaneously, transformational leadership style and employability provide a very significant role in influencing job satisfaction with p=0.000 (p less than 0.01); 2) Partially transformational leadership style provide a significant role on job satisfaction with p=0.019 (p less than 0.05); 3) Partially there was a very significant role of employability on job satisfaction with p=0.000 (p less than 0.01). Transformational leadership style and employability contribute 52.5% to job satisfaction. Employability contributed more dominantly to job satisfaction (35.8%) than the transformational leadership style (16.7%).